An exploratory study of factors associated with difficulties in accessing HIV services during the COVID-19 pandemic among Chinese gay and bisexual men in Hong Kong - Suen, Yiu Tung (Int J Infect Dis, 2021)
BACKGROUND: The coronavirus disease 2019 (COVID-19) pandemic has resulted in the disruption of provision of human immunodeficiency virus (HIV) services. This study examined the factors associated with difficulties in accessing HIV services during the COVID-19 pandemic. METHODS: An online survey of 236 Chinese-speaking gay and bisexual men in Hong Kong conducted in 2020. RESULTS: Among those who expressed a need to access HIV services during the COVID-19 pandemic, 22.9%, 33.9% and 43.2% indicated moderate-to-high, mild and no difficulties in accessing these services, respectively. Difficulties in accessing HIV services were positively related to concerns about potential COVID-19 infection, experience of actual impact on health because of COVID-19, disruption in work/studies, and reduced connection to the LGBT+ community during the pandemic. It was also found that difficulties in accessing HIV services were positively associated with frequency of having sex with casual partners, but were not significantly associated with frequency of having sex with regular partners. CONCLUSIONS: This study provides novel empirical evidence for understanding difficulties in accessing HIV services during the COVID-19 pandemic. It found that disruption in work/studies and frequency of having sex with casual partners were associated with difficulties in accessing HIV services.